2012
DOI: 10.12669/pjms.291.2733
|View full text |Cite
|
Sign up to set email alerts
|

Body dysmorphic disorder in aesthetic rhinoplasty candidates

Abstract: Objective: Body Dysmorphic Disorder (BDD) is a psychiatric disorder defined as obsessive ideas about distorted physical appearance, leading to social, professional and personal dysfunction. Many of these patients seek aesthetic surgery and are generally dissatisfied with the outcome of their surgery. In the present study patients coming to the otolaryngology clinic of Thaleghani Hospital in Tehran seeking rhinoplasty were evaluated. Methodology: Between October 2010 and October 2011, 130 patients seeking rhino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 19 publications
1
25
2
4
Order By: Relevance
“…Similarly, the most common Axis I diagnosis in the current study is the body dysmorphic (BDD) disorder (10.2%) while a lower rate (7%) was recorded by Sarwer and Crerand [28], on and the other hand, higher rates (24.5%, 32.5%, and 33%) were found by other investigators [18,29,30]. Differences could be attributed to different methods of assessment and diagnosis.…”
Section: Discussionsupporting
confidence: 43%
“…Similarly, the most common Axis I diagnosis in the current study is the body dysmorphic (BDD) disorder (10.2%) while a lower rate (7%) was recorded by Sarwer and Crerand [28], on and the other hand, higher rates (24.5%, 32.5%, and 33%) were found by other investigators [18,29,30]. Differences could be attributed to different methods of assessment and diagnosis.…”
Section: Discussionsupporting
confidence: 43%
“…There were improvements in the total study population across most nasal function outcomes ( Table 2) and in both groups ( Table 3 and Table 4). Rhinoplasty improved patient perceptions of nasal function with decreased sensation of nasal obstruction assessed by VAS on the left side (mean [SD] change, 18 [30]; P < .001) and VAS on the right side (mean [SD] change, 24 [30]; P < .001) and lower scores in disease-specific qualityof-life measures NOSE (mean [SD] change, 1.35 [1.21]; P < .001) and SNOT-22 (mean [SD] change, 0.81 [0.88]; P < .001). Additionally, there were improved scores in the nasal obstruction symptom for 74 of 88 patients (84.4%) (P < .001) and nasal function anchor score for 80 of 88 patients (90.4 0%) (P < .001) ( Table 2).…”
Section: Postoperative Changes In Nasal Function Outcomesmentioning
confidence: 99%
“…2 2 Anecdotally, men are less satisfied with cosmetic rhinoplasties than women. 24 However, previous studies 6,7,11,14,18,[24][25][26][27][28][29][30][31][32][33] have been unable to confirm whether satisfaction differs between the sexes because women make up the overwhelming majority of patients undergoing rhinoplasty. In this way, the demographic characteristics of populations undergoing rhinoplasty are a barrier to analyzing whether sex may influence patient satisfaction.…”
mentioning
confidence: 99%
“…The majority of patients in ‘unemployed’ group were housewives. [10] A study by Kalus and Cregan revealed an association between aesthetic plastic surgery procedure and job, in a term of satisfaction and burnout frequency. Plastic surgery practice was significantly associated with increased job satisfaction and fewer burnout episodes at work afterward.…”
Section: Discussionmentioning
confidence: 99%